PENGEMBANGAN ALGORITMA PENCARIAN RUTE DAN PEMBEBANAN LALULINTAS FUZZY - Kresnanto, Nindyo Cahyo; Tamin, Ofyar Z.; Bona F, Russ (Jurnal Transportasi, 2008)
AbstractÂ The path finding, called the Tree Building, is the main foundation on traffic assignment model. In conventional method, each iteration in route finding process can produce best path or shortest-path. On the contrary, on fuzzy travel cost condition, that process could produce several paths as shortest-path nominations. This paper discussed the route finding using fuzzy travel cost approach. In conventional method, travel cost, as an input in the model, is expressed in deterministic form, while in fuzzy cost, travel cost is represented as range of certain value from under-bound to upper-bound. Path finding process in fuzzy cost was developed based on Dijkstra (1959) algorithm which placed each selected route in certain layers. Layer with selected route is sequenced from âfirstâ best route. This algorithm is named as Dijkstra Multi Layer (DML) Algorithm. At the end, flow assignment has done with calculating fuzzy membership value in each selected route toward to the best route.Â Â Â Keywords: fuzzy route cost, shortest path, layer, Dijkstra Algorithm